Analisis Minat Nasabah Dalam Penggunaan Layanan Mobile Banking Pada Kspps Bmt Bahtera - Khodirotul Jannah, Nur; Al Husainah, Rohmah; Hafidz Ma’shum, AM (Jurnal BANSI - Jurnal Bisnis Manajemen Akutansi, 2022)
The basis of this research is the very fast development of data technology that makes people turn to the Mobile Banking framework to work with exchanges, but without direct contact whether it is in accordance with Islamic financial standards. This review plans to investigate the variables that cause customer premiums in using Mobile Banking. This examination is a subjective exploration with meeting information gathering procedures and documentation. The results showed that the premium of KSPPS BMT Bahtera Pekalongan customers for the use of Mobile Banking was controlled by 3 elements, especially the individual element starting from their own longing, the social element starting from the support of others or the interests of the foundation/office association. and elements of passion ranging from affection for accommodation, benefits, security and consolation.